The center-right in the transitions to democracy in Southern Europe: Between accommodation and (re)implantation or European political cultures (1974-1981) - González-Fernández, Ángeles (Historia y Política, 2022)
The political and social storm that unleashed the 2008 economic crisis has contributed to intensify and transfer to society the debate, installed in historiography since the 1990s, about democratizing process. Within the framework of this discussion, research on political parties, particularly on the centre-right, has taken on renewed interest in Spain, which is not unrelated to the phenomena of political polarization currently affecting liberal democracies and, in particular, the crisis of the party system that originated at that conjuncture, in contrast to the Portuguese and Greek experiences. The resilience of the model in these two countries, where the centre-right formations —the Social Democratic Party, PSD, and Nea Demokratia, ND— continue to play a key role in the political system, highlights the Spanish anomaly even though the early demise of Unión de Centro Democrático, UCD, did not mean the disappearance of centrism in Spain. Recognising the complexity of the concept of the political centre and the different formulations to which it can give rise, this article aims to re-examine the role played by centre-right political parties in the transition from dictatorship to parliamentary democracy in Portugal, Greece and Spain, in accordance with a transnational perspective and new approaches to political and social history.
Keywords: Democratic Transition; Southern Europe; political parties; center-right